Pengaruh Enterprise Risk Management Disclosure, Intellectual Capital Disclosure dan Debt to Asset Ratio terhadap Nilai Perusahaan - Leni Siti Rukmana Deffi; Dwi Cahyono; Rendy Mirwan Aspirand (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the effect of Enterprise Risk Management Disclosure, Intellectual Capital Disclosure and Debt To Asset Ratio on firm value. This research uses quantitative methods, involving a sample of 21 mining companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 period. Primary data is collected from regular company reports. The results of the study using a partial test showed a significance value of 0.397 for the Enterprise Risk Management Disclosure variable, a significance value of 0.349 for the Intellectual Capital Disclosure variable and a significance value of 0.301 for the Debt To Asset Ratio variable. The calculated coefficient of determination results obtained a value of 0.111, which means the independent variable under study only affects the value of the company by 11%, while the remaining 89% of the company's value is influenced by other independent variables outside the variables used in this study. Conclusions, Enterprise Risk Management Disclosure, Intellectual Capital Disclosure and Debt to Asset Ratio have no influence on firm value. Keywords: Enterprise Risk Management Disclosure, Intellectual Capital Disclosure and Debt To Asset Ratio, firm value.